Design of an HPPD fluorescent probe and visualization of plant responses to abiotic stress - Xiaoyan Zeng; Yurou Huang; Jing Dong; Xiaoxie Ma; Jia-Xu Nan; Weijie Chen; Hong-Yan Lin; Wen-Chao Yang; Xiaogang Liu; Jun Yin; Guang-Fu Yang (Advanced Agrochem, 2022)
The upregulation of 4-hydroxyphenylpyruvate dioxygenase (HPPD) can protect plants from adverse abiotic stress. Therefore, studying the changes of HPPD under abiotic stress is extremely valuable. In this study, we employed a rational molecular design strategy to prepare an HPPD-responsive fluorescent probe consisting of a pyrene fluorophore, a linker and a benquitrione skeleton recognition moiety that functions via an aggregation–disaggregation sensing mechanism. As predicted, this probe exhibited an obvious turn-on fluorescence response towards HPPD. In addition, in vivo imaging demonstrated the excellent capability of this probe to track HPPD in Arabidopsis thaliana, and the dynamic changes in HPPD were monitored under different stress degrees of high temperature and Cadmium (II) ion (Cd2+) stress. This work provides an efficient design strategy for acquiring a noninvasive HPPD fluorescence probe, which could evaluate the degree of stress and be further employed for exploring the stress resistance mechanism in plants.